PENGUJIAN PROSES BALANCING PADA BLOWER - Syaputra Arianto, Handika; Zulfiandi, Wendi; Sateria, Angga; Hasdiansah, Hasdiansah (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
This article discusses the balancing process on a blower using the 4-run method and the balancer feature on the Vibroport 80. The initial vibration measurement of the blower was recorded at 2.28 mm/s, with the impeller weighing 2.5 kg. After adding a 50-gram trial weight at an angle of 0°, the resulting vibration was 0.956 mm/s RMS. At 120°, the vibration measured 2.99 mm/s, and at 240°, it increased to 3.64 mm/s. Based on the calculations performed, a correction weight of 150 grams was determined at an angle of 20°, successfully reducing the vibration to 0.965 mm/s RMS. Using the balancer feature method, the initial vibration value of 1.91 mm/s gradually decreased to 1.36 mm/s after six stages of correction weight application. From the results of both tests, the 4-run method was found to be the most effective for balancing the blower